Adaptacja i egzotyzacja w przekazie nazw własnych (na materiale poezji dziecięcej Juliana Tuwima i Jana Brzechwy) - Manasterska-Wiącek, Edyta (Acta Polono-Ruthenica, 2006)
The aim of the article is to examine how proper names are delivered in the translation of J. Tuwim and J. Brzechwa’s poems for children into Russian. There appear so-called „sings of unfamiliarity” in the structure of the rendered text. They are connected with the change of a group of recipients of the poetry. We can talk about adaptation or exoticisation depending on the presence or lack of the „sings of unfamiliarity”. The presented analysis shows that there are more adaptation technignes (used in the translation of the verse). Owing to this strategy, the rendering corresponds with the age of the special reader and their perception of the world.